Neem Gum (Azadirachta Indica) Solution Potential for Improving Viability of Bifidobacterium Longum and Lactobacillus acidohilus Bacteria - Hamzah, Zahreni; Sulistyani, Erna; Hafizh, Cinantya; Handayani, Ari T.W. (Indonesia International Institute for Life Sciences, 2022)
Neem gum is a liquid that comes out of the stems of neem plants (Azadirachta indica) that have hardened and become crystals. Soluble polysaccharides compounds contained in this gum are composed of several types of monosaccharides such as arabinose, fucose, galactose, glucuronic acid, glucose, mannose, and xylose. The content of neem gum has prebiotic potential so it can be used as a source of nutrients for lactic acid bacteria. Bifidobacterium longum and Lactobacillus acidophilus are lactic acid bacteria classified as beneficial bacteria in the gastrointestinal tract. The content of soluble polysaccharides in neem gum can be selectively digested by these bacteria. This study aims to determine the potential of neem gum solution (Azadirachta indica) to the viability value of B. longum and L. acidophilus bacteria. The viability of B. longum and L. acidophilus bacteria was calculated using the MTT assay method. The results showed the viability value of both bacteria exposed to neem gum solution at concentrations of 5% (b/v), 10% (b/v), and 20% (b/v) increased compared to negative controls that were not given exposure to neem gum solution. Based on the results of the study, it concluded that neem gum is effective in increasing the growth of bacteria B. longum and L. acidophilus